Exergaming for Children and Adolescents: Strengths, Weaknesses, Opportunities and Threats - Benzing, Valentin (J Clin Med, 2018)
Exergaming, or active video gaming, has become an emerging trend in fitness, education and health sectors. It is defined as digital games that require bodily movements to play, stimulating an active gaming experience to function as a form of physical activity (PA). Since exergaming is becoming more popular, claims have been made on the usefulness of exergaming. It has, for example, been entitled as being “the future of fitness” by the American College of Sports Medicine, promoting PA and health in children and adolescents. However, research also suggests that long-term engagement in exergaming is difficult to achieve, and there is a noticeable reservation towards exergaming by parents, teachers and caregivers. To provide an overview and to outline the future directions of exergaming, the aim of this review was to critically illustrate the strengths, weaknesses, opportunities and threats of exergaming to promote PA and health in children and youth. The available evidence indicates that exergaming has the potential to improve health via an increase in PA. However, it seems that this potential is frequently underexploited, and further developments such as customized exergames are needed.